2022
DOI: 10.1186/s12882-022-02916-2
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis dissemination in kidney transplant recipient treated with anti-CD40 monoclonal antibody: a case report

Abstract: Background Tuberculosis (TBC) in solid organ transplant recipients represents a severe complication. The incidence among transplant recipients is higher than in the general population, and the diagnosis and treatment remain challenging. We present a case of active disseminated tuberculosis in a kidney transplant recipient treated with an anti-CD40 monoclonal antibody, who had been previously exposed to an active form of the disease, but latent tuberculosis (LTBI) was repeatedly ruled out prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… 12 As in this case, non-caseous necrosis has been reported in a biopsy of a patient infected with TB after kidney transplantation. 13 One study reported that a patient with human immunodeficiency virus-1 (HIV-1) and pulmonary TB showed the presence of fewer necrotic granulomas and less pulmonary cavitations. 14 On the other hand, completely opposite results have been reported that HIV-1 and TB co-infected patients have more poorly formed and necrotic lymph nodes than HIV-1 negative patients.…”
Section: Discussionmentioning
confidence: 99%
“… 12 As in this case, non-caseous necrosis has been reported in a biopsy of a patient infected with TB after kidney transplantation. 13 One study reported that a patient with human immunodeficiency virus-1 (HIV-1) and pulmonary TB showed the presence of fewer necrotic granulomas and less pulmonary cavitations. 14 On the other hand, completely opposite results have been reported that HIV-1 and TB co-infected patients have more poorly formed and necrotic lymph nodes than HIV-1 negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the CD40/CD154 pathway may therefore potentiate the reactivation of latent cysts in cerebral and ocular tissue with consequent parasite proliferation and tissue damage. The role of the CD40/CD154 pathway in eliciting cell-mediated immunity in the defense against intracellular infection has also been demonstrated by a case of latent tuberculosis reactivation in a renal transplant patient on iscalimab [ 11 ]. This patient's age and recent systemic corticosteroids and mycophenolate mofetil are also likely to have contributed to his immunodeficient state.…”
Section: Discussionmentioning
confidence: 99%